(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study confirms the need for pre Islamic poetry with its symbols,and functions for anew in - depth reading that shows the text as expressive energy. Based in many of its symbols and functions on mythological dimensions, preset in a poetic text, a professionally employed to respond to psychic quirks, the research is based on reading the scene of sacrifice, in light of a textual study that uses artistic images as means of expression, through which the poets tried to download the pagan religious ritual an emotional overflow related to the meth concept, but through it symbolizes ideas and positions that are far from thepurely religious character, it has its technical configurations after treating the texts affixed in it, the research proceeds to confirm the artistic richness of the symbol of sacrifice in pre Islamic poetry, As it provides a tremendous ability to reveal intellectual, and psychological dimensions in every textual reading . the research found that the symbol of the sacrifice in Arabic poetry before Islam it was a way to expressing the poets attitudes, ideas and visions of issues of existence and life, and the aim of their about it was not to mention the mythological origins, but rather to employ it and artistic functions according to their emotional potentials.